Sosialisasi Dan Workshop Pembuatan Eco-Enzyme Di Kelurahan Teluk Betung, Kecamatan Teluk Betung Selatan, Kota Bandar Lampung - Ammara Augistin; Zhona Trisyabila; Kania Ramadhita; Cut Ubiet Ahsanti (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Organic waste, particularly fruit peels and food scraps, remains a major issue in Indonesia and contributes significantly to environmental pollution. One eco-friendly solution is the utilization of eco-enzyme, a liquid produced through the fermentation of organic waste, which serves as liquid fertilizer, household cleaner, and waste decomposer. This community service program aimed to improve the knowledge and skills of residents in Teluk Betung Village, Teluk Betung Selatan District, Bandar Lampung City, in managing organic waste through socialization and eco-enzyme production workshops. The methods included lectures, discussions, hands-on practice, and evaluation using pre-tests and post-tests. The results revealed high enthusiasm from 22 participants, with a notable increase in understanding, as indicated by an average post-test score of 89 compared to the pre-test average score of 44. This training provided the community with a simple solution to reduce household organic waste while producing valuable and sustainable products for daily use.